KEGIATAN PEMBELAJARAN TK BUMI UKIR BERBASIS KEARIFAN LOKAL BUDAYA DI JEPARA - Anita Afrianingsih; Indah Sa'adah; Ika Puji Astuti; Aulia Putri Salsabillah; Miladia Haritsa Junaidi; Nanik Farida; Fitriani Nor Hidayah; Al Musdalifah (FKIP Universitas sriwijaya, 2021)
Culture, being a very important thing to instill in early childhood, local culture, especially where children live, plays an important role in shaping children's character in receiving learning about themselves and their world, introducing local culture to children from an early age serves to instill attitudes, behaviors, personalities and manners, love the country and foster a spirit of nationalism in children. The purpose of this research on learning activities based on local cultural wisdom in Jepara is to introduce the values of local cultural wisdom in Jepara to early childhood and to examine more deeply about local culture-based learning models. The approach method used is a case study qualitative research method with data collection methods carried out through observation and through several activities, namely planning, model design, material procurement and curriculum and media trials based on local cultural wisdom. APE SINDU stands for Sinau Budoyo. The subjects of this study were children aged 5-6 years. The results of this activity research indicate that learning activities based on the wisdom of local culture in Jepara using the SINDU educational game tool can make it easier for children to get to know and know the local culture in Jepara, learning is also more interesting and interactive.